Perfil epidemiológico de la infección por SARS-COV-2 en pediatría - Mario Bustos-Paz (Asociación Colombiana de Infectología, 2023)
Objective: To describe the epidemiological and clinical profile of pediatric patients who were treated for suspected COVID-19 infection, between March and Octo-ber 2020, at the Hospital Universitario San Ignacio (HUSI), in Bogotá, Colombia. Materials and methods: Cross-sectional design. Description of patients aged 1 month to 1 day before their 18th birthday, assessed between March and October 2020, who were approached by any pediatric care service of a university hospital for suspected COVID-infection. 19, according to current national and institutional protocols. Demographic variables and the reason for consultation of all individuals with suspected infection were recorded. Only when SARS-CoV-2 infection was confirmed were variables related to clinical aspects of the disease and its evolution recorded. Results: 920 medical records of pediatric patients with suspected SARS-CoV-2 infection were evaluated, of which there were 157 confirmed cases with COVID-19 infection. The main reason for consultation to suspect infection was fever in 50% of the cases. In patients with virological confirmation, 32.48% of the cases at-tended required hospital management. MIS-C was suspected in 5 patients who required intensive care unit management. In the evaluated period, there were no deaths associated with COVID-19 infection.Conclusions: SARS-CoV-2 infection is related in most cases to a spectrum of mild disease in the pediatric population. This study may be larger than pediatric patients presenting with gastrointestinal rather than respiratory symptoms, and the frequency of renal complications should be taken into account in patients in whom the systemic inflammatory syndrome associated with COVID-19 is suspected.